Pengaruh Sasaran Anggaran, Kompetensi dan Teknologi Informasi Terhadap Akuntabilitas Dana Desa di Kerambitan, Tabanan - Gusti Ayu Putu Wiwik Anggraeni; Cokorda Gde Bayu Putra; Ni Ke Muliati (Hita Akuntansi dan Keuangan, 2023)
Accountability for the management of village funds should always be given due consideration in coordinating clarity of budget targets, capacity of village human resources, and maximum use of information technology that can support proper management of village funds. need to do it. The purpose of this study is to determine the impact of budget target clarity, human resource capacity and the use of information technology on accountability for village fund management (an empirical study in Kerambitan District). For the sampling method using Jenuh sampling, the number of samples is 120 samples. The conclusion of this study is that clarity of budget targets, human resource capacity, and information technology have a positive and significant impact on village fund management accountability. The proposal will improve the village's financial management by clarifying the target of the working budget, enhancing the capacity of staff and making the best use of information technology